Doublet decoding of tRNASer3 demonstrates plasticity of ribosomal decoding center - Shruthi Krishnaswamy; Shirin Akbar; Daniel S. D. Larsson; Yang Chen; Maria Selmer (Nature Communications)
Abstract Frameshifts can be caused by specific combinations of tRNA and mRNA. The wildtype AGC-decoding E. coli tRNASer3 GCU has been shown to induce −1 ribosomal frameshifting on GCA alanine codons, and proposed to read a two-base codon instead of a canonical triplet. However, it has remained unclear whether this type of non-cognate decoding can be accommodated by the ribosome. Here, we perform single-particle cryo-EM reconstructions on E. coli 70S ribosomes with the frameshift-inducing tRNASer3 bound to the non-cognate GCA codon or the cognate AGC codon in the ribosomal A site. The structures demonstrate that doublet decoding is made possible when A1493, the conserved monitoring base in 16S rRNA, mimics a first codon base, forming a Hoogsteen base pair with U36 from the anticodon and stacking with the mRNA. This interaction pushes the first two bases of the A-site codon in position for base pairing with C35 and G34 of the anticodon.